The Implementation of Micro Small Medium Enterpise (MSME) Accounting in Credits to Financial Institutions - Rakhmini Juwita (Budapest International Research and Critics University, 2021)
MSME can encourage economic growth, social stability, and the development of the business world in Indonesia. Hence, the government attempts to increase MSME competitiveness to become a sustainable business on a larger scale. To realize this, MSME requires additional capital through bank loans. The purpose of this study is to determine the implementation of accounting at MSME in three provinces that have the most MSMEs, i.e., West Java, Central Java, and East Java. Moreover, this study also purposes at revealing the effect of accounting implementation on credit to financial institutions. This study involved seventy-five MSME respondents. The results of the study indicated that the implementation of accounting at MSMEs in the Provinces of West Java, Central Java, and East Java had been well implemented. However, the provision of credit by financial institutions was still considered sufficient since lending by financial institutions was not in accordance with the loan application proposed by MSMEs.